Patients with High Pelvic Tilt Achieve the Same Clinical Success as Those with Low Pelvic Tilt After Minimally Invasive Adult Deformity Surgery. Issue 2 (17th August 2017) - Uribe, Juan S; Januszewski, Jacob; Wang, Michael; Anand, Neel; Okonkwo, David O; Mummaneni, Praveen V; Nguyen, Stacie; Zavatsky, Joseph; Than, Khoi; Nunley, Pierce; Park, Paul; Kanter, Adam S; et al.
Abstract: BACKGROUND: Pelvic tilt (PT) is a compensatory mechanism for adult spinal deformity patients to mitigate sagittal imbalance. The association between preop PT and postop clinical and radiographic outcomes has not been well studied in patients undergoing minimally invasive adult deformity surgery. OBJECTIVE: To evaluate clinical and radiographic outcomes in adult spinal deformity patients with high and low preoperative PT treated surgically using less invasive techniques. METHODS: Retrospective case-control, institutional review board-approved study. A multicenter, minimally invasive surgery spinal deformity patient database was queried for 2-yr follow-up with complete radiographic and health-related quality of life (HRQOL) data. Hybrid surgery patients were excluded. Inclusion criteria were as follows: age > 18 and either coronal Cobb angle > 20, sagittal vertical axis > 5 cm, pelvic incidence-lumbar lordosis (PI-LL) > 10 or PT > 20. Patients were stratified by preop PT as per Schwab classification: low (PT< 20), mid (PT 20-30), or high (>30). Postoperative radiographic alignment parameters (PT, PI, LL, Cobb angle, sagittal vertical axis) and HRQOL data (Visual Analog Scale Back/Leg, Oswestry Disability Index) were evaluated and analyzed. RESULTS: One hundred sixty-five patients had complete 2-yr outcomes data, and 64 patients met inclusion criteria (25 low, 21 mid, 18 high PT). High PT group had higher preop PI-LL mismatch (32.1 vs 4.7; P < .001). At last follow-up, 76.5% of patients in the high PT group had continued PI-LL mismatch compared to 34.8% in the low PT group ( P < .006). There was a difference between groups in terms of postop changes of PT (–3.9 vs 1.9), LL (8.7 vs 0.5), and PI-LL (–9.5 vs 0.1). Postoperatively, HRQOL data (Oswestry Disability Index and Visual Analog Scale) were significantly improved in both groups ( P < .001). CONCLUSION: Adult deformity patients with high preoperative PT treated with minimally invasive surgical techniques had less radiographic success but equivalent clinical outcomes as patients with low PT.